STRATEGI DAKWAH KULTURAL USTADZ ZAINAL ARIFIN DI DUSUN BIYORO, KEDIRI - Ummy Fadillah; Muhamad As’ad (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to describe the cultural da'wah strategy implemented by Ustadz Zainal Arifin in Biyoro Hamlet, Kandangan Village, Kandangan District, Kediri Regency. Cultural da'wah refers to a preaching approach that integrates Islamic values with local culture. This research used a descriptive qualitative method with data collection techniques including observation, in-depth interviews, and documentation. The results show that Ustadz Zainal Arifin employed a strategy of Islamizing local traditions through activities such as Barikan and religious gatherings, gradual and empathetic approaches, exemplary behavior, and effective interpersonal communication. These strategies have led to increased religious understanding and practices among the community. Supporting factors include the active role of the preacher, support from local leaders, and a humanistic approach. Hindering factors include low education levels and strong adherence to traditional Javanese beliefs. This research is expected to serve as a reference for culturally adaptive da'wah development.